Exploring Students' Perspectives of The Use Audio-Visual in English Listening SKill - Nur Rahma Maulida M; Munir; Geminastiti Sakkir; Adeliah Nurmuthmainnah Syam; Nurfitrah Awaliyah (Universitas Islam Negeri Palopo, 2025)
This study aims to explore students’ perspectives on the use of audio-visual media in learning English listening skills. Employing a descriptive qualitative research design, the study involved six students from Grade XI at SMAN 2 Pangkep. Data were collected through semi-structured interviews and documentation. The findings indicate that students generally hold positive views toward the use of audio-visual media. They perceive it as an effective tool that enhances their engagement, increases motivation, and facilitates a better understanding of listening materials. Students reported that the combination of sound and visual elements helped them grasp meaning more easily, making the learning process more enjoyable and less monotonous. Their perspectives also highlight the role of audio-visual media in supporting active participation, reinforcing comprehension through imagery, and encouraging independent learning. These insights suggest that audio-visual media can be a valuable resource in developing English listening skills from the learners’ point of view.